MARKET RESEARCH FOR MULTIFUNCTION SALON CABINET - Santoso, Elizabeth Clara; Juyanto, Jennifer; Ajipangestu, Mario; Gozali, Lina; Daywin, Frans Jusuf; Sukania, I Wayan; Kosasih, Wilson; Adianto , Adianto; Doaly, Carla Olyvia; Mutiara, Maitri Widya (International Journal of Application on Economics and Business, 2023)
Multifunction Salon Cabinet is a salon cabinet that has a high selling value carried out through mass production of the Multifunction Salon Cabinet. Beauty businesses such as salons are in great demand by the public, because in addition to being able to treat the appearance from the top to the bottom of our body, such as hair care, face, hands, feet, and even the skin. Everyone, especially women, cares about their bodies, so the beauty business never loses interest. Economic analysis and added value are important things to do for business continuity. The R-value of the data validity test table with the number of 200 respondents. The calculated R-value for each variable above the table R, so it has been proven that all data collected is valid. The results of reliability testing using the SPSS application, a Cronbach's Alpha value was obtained. It is known that if alpha > 0.7 means that reliability is sufficient, so this test is reliable. Based on the results of the calculation above, a consistency ratio (CR) value was obtained. These results indicate that data consistency is acceptable with a CR value of < 0.1.